A Note on the Generalized Carleman Boundary Value Problem for the System with Constant Coefficients of the Class E2 (Journal of Partial Differential Equations, 1989)
The main purpose of this note is to consider the generalized Carleman boundary value problem for the elliptic equations with constant coefficients of the second type in the simple connected domain of complex plane. Making use of Fredholm integral equations and the classica1 theory of the boundary value problem for analytic functions, we obtain the existence, uniqueness and the representation of solution for above Carleman boundary value problem.